Prevalence and factors associated with the poor quality of sleep among Indian nurses - Jasneet Kaur; Sheela Upendra; Sheetal Barde (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Nursing health workers deal with a variety of issues that may have an unfavorable influence on their capability to peaceful sleep. The consequences of poor quality of the sleep can lead to increased fatigue, decreased concentration, and a higher risk of medical and nursing errors. The purpose of this research study was to determine in the occurrence and associated factors for poor quality of the sleep among Indian nurses. MATERIALS AND METHODS: The participants in this cross-sectional study were selected by the use of a multi-stage sampling technique. A total of 25 hospitals (across 4 zones) were randomly sampled. A total of 850 (out of 1250) nurses participated in the study. To collect socio-demographic data, a self-administered questionnaire was employed. PSQI scale was implemented to assess quality of sleep, and the other scale of DASS-21 was used to assess mental well-being. RESULTS: The majority of nurses had mild (6-7 hours) as well as moderate (5-6 hours) levels of difficulty in the duration of sleep time. The occurrence of poor quality of the sleep in nursing professionals is high. 9.2% had depression, 13.7% had anxiety, and 18.9% faced, which appears to be linked to insufficient sleep in the adjusted model. In the univariate study, additional night shifts and additional shift hours were substantially related to insufficient sleep. CONCLUSION: Nurses' quality of sleep is substantially hampered due to various reasons, and nurse mangers should devise the framework to avoid its harmful effects and to provide desirable management and high-quality patient care.